Predicting mortality in cardiogenic shock secondary to ACS requiring short‐term mechanical circulatory support: The ACS‐MCS score. Issue 7 (7th March 2021) - Marashly, Qussay; Taleb, Iosif; Kyriakopoulos, Christos P.; Dranow, Elizabeth; Jones, Tara L.; Tandar, Anwar; Overton, Sean D.; Tonna, Joseph E.; Stoddard, Kathleen; Wever‐Pinzon, Omar; Kemeyou, Line; Koliopoulou, Antigone G.; et al.
Abstract: Objective: To identify predictors of 30‐day all‐cause mortality for patients with cardiogenic shock secondary to acute coronary syndrome (ACS‐CS) who require short‐term mechanical circulatory support (ST‐MCS). Background: ACS‐CS mortality is high. ST‐MCS is an attractive treatment option for hemodynamic support and stabilization of deteriorating patients. Mortality prediction modeling for ACS‐CS patients requiring ST‐MCS has not been well‐defined. Methods: The Utah Cardiac Recovery (UCAR) Shock database was used to identify patients admitted with ACS‐CS requiring ST‐MCS devices between May 2008 and August 2018. Pre‐ST‐MCS clinical, laboratory, echocardiographic, and angiographic data were collected. The primary endpoint was 30‐day all‐cause mortality. A weighted score comprising of pre‐ST‐MCS variables independently associated with 30‐day all‐cause mortality was derived and internally validated. Results: A total of 159 patients (mean age, 61 years; 78% male) were included. Thirty‐day all‐cause mortality was 49%. Multivariable analysis resulted in four independent predictors of 30‐day all‐cause mortality: age, lactate, SCAI CS classification, and acute kidney injury. The model had good calibration and discrimination (area under the receiver operating characteristics curve 0.80). A predictive score (ranging 0–4) comprised of age ≥ 60 years, pre‐ST‐MCS lactate ≥2.5 mmol/L, AKI at time of ST‐MCS implementation, and SCAI CS stage E effectively risk stratified our patient population. Conclusion: The ACS‐MCS score is a simple and practical predictive score to risk‐stratify CS secondary to ACS patients based on their mortality risk. Effective mortality risk assessment for ACS‐CS patients could have implications on patient selection for available therapeutic strategy options.